2007
DOI: 10.1037/0012-1649.43.3.564
|View full text |Cite
|
Sign up to set email alerts
|

Involvement in traditional and electronic bullying among adolescents.

Abstract: The increasing availability of Internet and cell phones has provided new avenues through which adolescents can bully. Electronic bullying is a new form of bullying that may threaten adolescent social and emotional development. In this study the relation between involvement in electronic and traditional bullying was examined. Eighty-four adolescents completed questionnaires regarding their involvement in traditional and electronic bullying. Results show that students' roles in traditional bullying predicted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

44
527
6
70

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 763 publications
(647 citation statements)
references
References 39 publications
44
527
6
70
Order By: Relevance
“…The hypothesis that t-victims, protected by the anonymity provided by technology, would engage in c-bullying in order to take revenge was not supported and so provides support for previous work (e.g. Raskauskas & Stoltz, 2007;Slonje & Smith, 2008). Our findings imply that children are either bullies or victims inside and outside school and that anonymity, while perhaps facilitating indirect bullying does not incline people who are not bullying orientated into bullying activity even if they have the prospect of revenge.…”
Section: Bullying and Cyberbullying 23 23supporting
confidence: 66%
See 4 more Smart Citations
“…The hypothesis that t-victims, protected by the anonymity provided by technology, would engage in c-bullying in order to take revenge was not supported and so provides support for previous work (e.g. Raskauskas & Stoltz, 2007;Slonje & Smith, 2008). Our findings imply that children are either bullies or victims inside and outside school and that anonymity, while perhaps facilitating indirect bullying does not incline people who are not bullying orientated into bullying activity even if they have the prospect of revenge.…”
Section: Bullying and Cyberbullying 23 23supporting
confidence: 66%
“…However, this was not supported by subsequent studies in adolescents (Raskauskas & Stoltz, 2007;Slonje & Smith, 2008). Raskauskas & Stoltz found that students' role in t-bullying predicted the same role in c-bullying, and moreover, being a t-bully was associated with c-victimization.…”
Section: Bullying and Cyberbullying 8mentioning
confidence: 79%
See 3 more Smart Citations